Troubling Secondary Victimization of Bullying Victims: The Role of Gender and Ethnicity - Carrera Fernández, María Victoria (Journal of interpersonal violence, 2022)
Bullying is a severe public health problem, and bystanders? reactions are a key variable in its perpetration and maintenance. This study aimed to assess the level of secondary victimization of bullying victims as a function of the student?s sex and the victim?s category (nonnormative vs. normative) in three experimental conditions (feminine, masculine, and ethnicity) from a socioecological perspective. Specifically, two dimensions of secondary victimization were evaluated: avoidance and devaluation/blaming of the victim. A sequence of mixed-design ANOVAs was performed with a sample of 553 Spanish (53.3%) and Portuguese (46.7%) students, aged between 14 and 19 years. Results show that nonnormative victims, those who transgress feminine and masculine gender stereotypes, and those who belong to a minority ethnic group (gypsies) are avoided more than normative victims; and that boys perpetrate more secondary victimization than girls. These results reveal the situation of vulnerability suffered by adolescents who transgress the gender norm as well as those who belong to minority ethnic groups, and highlight that the motivations concealed by the secondary victimization of bullying victims originate in the group processes of identity construction and categorization that configure the boundaries of ?legitimacy? and are strongly influenced by social beliefs about normative and nonnormative identities. This socioecological approach could guide prevention strategies, so generic antibullying policies that do not explicitly address biases about gender, sexual, and cultural identity can be overcome to reduce the high levels of stigma occurring in the schools through critical and culturally responsive pedagogy.